Enhancing writing skills and language creativity through the plus-minus-interesting technique: A case study at the primary school level - Isah Cahyani; Jatmika Nurhadi; Mentari Mentari (Indonesian Journal of Applied Linguistics, 2023)
Language creativity plays a pivotal role in facilitating effective communication, especially in written expression. Proficient writing skills require a dedicated teaching and learning process that nurtures critical thinking abilities. While the significance of language creativity and writing skills has been acknowledged, empirical research focusing on explicit techniques to enhance these skills among young learners is needed. Addressing this research gap, this study explores the impact of integrating the PMI (Plus-Minus-Interesting) technique, an integral component of the Cognitive Research Trust framework, in teaching narrative text to primary school students. Employing a case study research method, this study involves 67 students, with data collected through observations, interviews, and analysis of selected students' multiple drafts. The findings reveal significant improvements across various aspects of students' written texts, including word count, vocabulary usage, flow, and organizational structure, following the implementation of the PMI technique. Observations demonstrate that students displayed heightened levels of active engagement and expressive writing when utilizing the PMI technique, effectively incorporating 'plus', 'minus', and 'interesting' elements from their personal experiences. This integration enhanced their overall written communication skills. Based on the study's results, the PMI approach provides clear and structured instruction in literacy learning and development. It particularly offers a practical approach for nurturing language creativity and improving writing skills among young learners.